2005
DOI: 10.1002/jbm.a.30506
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant inhibition of poly(carbonate urethane) in vivo biodegradation

Abstract: This study compared the effect of an antioxidant on the in vivo biodegradation of a poly(carbonate urethane) (PCU) and a poly(ether urethane) (PEU). Unstrained PEU and PCU films with and without Santowhite were implanted subcutaneously into 3-month-old Sprague-Dawley rats for 3, 6, and 12 months. Characterization of unstabilized PEU and PCU with ATR-FTIR and SEM showed soft-segment and hard-segment degradation consistent with previous studies. In particular, evidence of chain scission and crosslinking of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(104 citation statements)
references
References 32 publications
9
91
4
Order By: Relevance
“…The soft segment of polyether polyurethanes is known to undergo degradation. [86][87][88][89][90][91][92][93][94][95][96][97][98] This phenomenon will be discussed in the next section.…”
Section: Mediators Of Degradation-mentioning
confidence: 97%
See 1 more Smart Citation
“…The soft segment of polyether polyurethanes is known to undergo degradation. [86][87][88][89][90][91][92][93][94][95][96][97][98] This phenomenon will be discussed in the next section.…”
Section: Mediators Of Degradation-mentioning
confidence: 97%
“…Polycarbonates were used as the soft segments in these polymers and exhibited a marked reduction in degradation. [96] A fourth generation of polyurethanes is currently under investigation. These polyurethanes have soft segments that are either polyether or polycarbonate but, more importantly, have short chain molecules attached to the polymer chain ends (SME, surface modifying endgroups) such that when fabricated, these adhesion inhibiting molecules are present at the surface of the biomaterial at the tissue/material interface.…”
Section: Device Failurementioning
confidence: 99%
“…Furthermore, we would expect to see slowed in vivo release kinetics through suppression of ROS via antioxidants or other means. In fact, a number of studies 59,42,60,5 have shown decreased in vivo degradation of biodegradable polymers through the delivery of antioxidants to the local implant site. This particular study set has not been replicated herein due to the need to retrospectively fit the ROS suppression kinetics as a function of antioxidant concentration and reactivity with ROS.…”
Section: Other Possible Accelerated Degradation Mechanismsmentioning
confidence: 98%
“…[83][84][85][86] With respect to pacemaker leads, which commonly use polyurethane insulation, the duration from implantation to device failure has been shown to be as short as $2.5 years. 87 Laboratories, including our own, have tried to address the issue of oxidative degradation of polyurethane by coblending 84 or covalently linking 86,88 phenol-based antioxidants to polyurethane preparations. The limitations of this approach lie primarily in the fact that the antioxidants are expended once they react with hydroxy radicals.…”
Section: Cd47-modified Polymersmentioning
confidence: 99%